A escrita de crônicas para divulgação em rádio: uma proposta de estímulo à produção textual - Antonieta Aparecida Lima Ciara (2021)
This research, developed within the scope of the Professional Master's Degree in Languages, has as its object the elaboration of a didactic sequence in order to fill pedagogical and theoretical gaps with regard to the development of discursive competences in text production at school. In this context, the target audience is 9th grade students. For that, the research methodology, starting from the mobilization of contents and practices, conformed in a didactic sequence, presents a proposal for intervention of a propositional character. Among the various objectives of the research, it is worth highlighting the purpose of developing a didactic sequence that contributes to the knowledge of the structure of the chronicle genre and its purposes, and, likewise, as well as intensifying the reading of texts as a way of expanding and developing the critical thinking of the student, with a view to consolidating man as a social and historical being. For this, we will use semiotics in the presentation of themes for the production of the chronicle, as a method for reflection on the social issues in which the student is directly and indirectly inserted, enabling the breaking of the existing barrier between the student and the practice of textual production, through the appreciation of the reflections made orally by them, during the reading and analysis of the texts. We hope to contribute to the preparation of the student so that they can assume the role of speaker, organizing their speech with a greater degree of clarity, so that the interaction with the listening public is successful, since the texts will be disseminated in a program of radio. To support the analysis of interaction and dialogism, we start from the principles of Bakhtin (1997), as well as Geraldi (2012; 2015), Marcuschi (2008; 2012) and Rojo (2009), with regard to the concept of gender and multiliteracies. In Cândido (1992), Ferreira (2008), Thomé (2015) and Baltar (2012) we found support in relation to the conception of gender in the discourse, chronicles and knowledge about radio. The research dialogues with the BNCC – Base Nacional Comum Curricular (BNCC): Educação Infantil e Ensino Fundamental (BRASIL, 2018). The teaching of Portuguese at BNCC (BRASIL, 2018) is anchored in the socio-interactionist conception of language in which dialogy, the result of human interactions, occupies a central place. With regard to methodology, we used the didactic model of Dolz, Noverraz and Schneuwly (2004). Per application of didactics sequences included in this work we believe it is possible provide to the students new relations with culture and writing in special, assuring the development of capacities to produce texts related to the textual genre chronicle.